Epidemiological Characteristics and Drug Resistance of Fungemia in General Hospitals from 2010 to 2019. (2nd November 2021) - Bai, Yanling; Zheng, Zhigang; Liu, Ting; Yan, Zhongqiang; Du, Mingmei; Yao, Hongwu; Liu, Yunxi; Suo, Jijiang
Abstract : Objective . This study intends to analyze the data of fungemia in a large tertiary hospital from 2010 to 2019, and is aimed at understanding its epidemic characteristics and drug resistance. Methods . The "Hospital Infection Real-Time Monitoring System" was used to retrieve the case information of patients who were hospitalized for more than 48 hours from 2010 to 2019. The questionnaire was designed to collect patients' basic information, infection situation, drug resistance, and other related information. Statistical software was used for analysis. Results . The fungi detection rate was in the range of 0.19% 0.75% in ten years, the average rate was 0.29%, and the rate 0.2% 0.3% since 2013, which was lower than that from 2010 to 2012. Non- Candida albicans was the main fungus, accounting for 62.50%. The drug resistance of non- C. albicans was higher than that of C. albicans, among which C. glabrata had the highest resistance rate. Data analysis showed that the patients with more serious basic diseases, combined with infection of other sites, surgery, long hospital stay, combination of antibiotics, and invasive catheterization, were more likely to occur fungemia. Conclusion . We should pay more attention to the patients with high-risk factors of fungemia and focus on the drug resistance of non- C. albicans, choose the right antifungal drugs, so as to improve the level of diagnosis and treatment.